(untitled) (Global Journal of Management and Business Research, 2020)
The objective of this study is to assess the role of the Accounting information in the decision of granting bank credit to Cameroonian enterprises. Given to the problem of information asymmetry that prevails in the banking environment, we have used an approach that mobilizes the agency theory, the theory of transaction costs and theory of financial intermediation. Our empirical study was based on a qualitative approach. It consisted of a case study on a sample of eleven bankers of different banks in the cities of Bafoussam and Dschang. The primary data collection was conducted through an interview guide and the Opinions were recorded, or written. Given to the quantitative and qualitative information gathered, the use of the method called "triangulation" allowed to present the results of our study. According to these results, we have found that: a) perception of bankers on the Accounting information presented to them by businesses to obtain credit is not good, so there are not satisfied with this information; because some they are full of flaws either due to manager’s ignorance or in function of the objectives to attain by the firms’ manager.